Community phylogeny and spatial scale affect phylogenetic diversity metrics in a species‐rich rainforest in Borneo. Issue 11 (22nd November 2022) - Okuno, Seiya; Yin, Tingting; Nanami, Satoshi; Matsuyama, Shuhei; Kamiya, Koichi; Tan, Sylvester; Davies, Stuart J.; Mohamad, Mohizah; Yamakura, Takuo; Itoh, Akira
Abstract: Community phylogenetic analysis is an effective approach to understanding the process of community formation. The phylogenetic tree of the species pool is reconstructed in the first step, and the phylogenetic tree obtained in the second step is used to analyze phylogenetic diversity. Sythetic trees have often been used in the construction of phylogenentic trees; however, in tropical rainforests with many closely related species, synthetic trees contain many unresolved nodes, which may affect the results of phylogenetic structure analysis. Here, we constructed a phylogenetic tree using DNA barcode sequences ( rbcL, matK, trnH‐psbA ) for 737 tree species from the rainforests of Borneo, which have a high‐species diversity and many closely related species. The phylogenetic tree had fewer polytomies and more branch length variations than the Phylocom synthetic trees. Comparison of community phylogenetic analyses indicated that values of the standardized effect size of mean pairwise distance (SES–MPD) were highly correlated between Phylocom and DNA barcode trees, but less so for the standardized effect size of mean nearest taxon distance (SES–MNTD), suggesting that caution is needed when using synthetic trees for communities containing many congeneric species, especially when using SES–MNTD. Simulation analysis suggested that spatial dependence on phylogenetic diversity is related to the phylogenetic signal of the species' habitat niche and the spatial structure of habitat, indicating the importance of detailed phylogeny in understanding community assembly processes. Abstract : We determined DNA barcode sequences of 737 tree species in the Borneo rainforest, which has a high species diversity with many closely related species. Comparative analysis of community phylogeny suggested that caution should be exercised in the use of synthetic phylogenetic trees constructed with Phylocom and other tools for highly diverse forests. Simulation analysis was also conducted to demonstrate the significance of DNA barcode phylogeny in the study of community assembly processes.